Effect of different surface treatments on the roughness of porcelain layer for all ceramic restoration. - Maryam Jawad Challo; Shatha Abdulla Salih (Erbil Dental Journal)
Background: porcelain layered zirconia restoration fractures are serious and create an aesthetic and functional dilemma for the patients and the dentist. This demands the development of practical repair options that do not necessitate removing and remaking entire restorations. The roughness of the porcelain surface before repairing material application is considered a critical step.